Sociology of education in India - Jayaram, N. (New Delhi Rawat Publications, 2015)
Sociology of education is defined as a sociological study of the institutions and processes of education, on the one hand, and the relation between education and the other facets of society, on the other. This book provides an introduction to this subject and analyzes various themes under its umbrella by focusing on Education in India. Part I of the book introduces sociology of education; analyzes the relation between education and society, in general, and between the school and the community, in particular; and outlines the social History of education in the country. Part II deals with the issues in and perspectives on the relation between education, employment, and economy. Part III analyzes the relation between education, inequality, and social Change. It also discusses the concept of 'value-oriented education' And reflects on the educational backwardness of Muslims. Part IV examines the decline of the University as a public institution, the changing status of the academic profession, and the nature of student political activism. Part V dwells on the political aspects of education by discussing the issues of multiculturalism, democracy, peace, and conflict - all in relation to education. [Subject: India studies, education].
Keywords: Educational sociology--India